Potensi Ruang Spasial Untuk Ketahanan Pangan Masyarakat Di Kelurahan Langkai Kota Palangka Raya: Spatial Potential for Community Food Security in Langkai Subdistrict, Palangka Raya City - Hamidah, Noor; Nindito, Dwi Anung; Syahrozi, Syahrozi; Nazwa, Nazwa; Mahmudah, Noor (HUTAN TROPIKA, 2024)
Palangka Raya City is the capital of Central Kalimantan Province which is crossed by the Kahayan River Basin. The residential area is located on the Kahayan Riverside area which is filled with residences, one of which is in Langkai Village, Pahandut District. The shape of the houses in the Langkai Village residential area is linear and refer to the pattern of the Kahayan River. This research objectives to analyze the potential of spatial space in Langkai Village on the Kahayan Riverside area, Palangka Raya City. The research method is qualitative including literature study (secondary data) and primary data from interviews and field observations. The research stage includes literature study at the preparation stage, the implementation stage is direct observation and in-depth interviews, and the post-implementation stage is spatial figure ground analysis, namely; solid and void, road patterns through linkage analysis, as well as place analysis of the particularities of riverside areas and their development. The results of the regional analysis include: spatial space utilization, road accessibility patterns, open space activities, and identity potential in the Kahayan Riverside area, Langkai Village, Palangka Raya City.